Evaluation of cepheid GeneXpert MTB/RIF assay for Mycobacterium tuberculosis detection and rifampicin resistance in clinical specimen - Zahoor, Danish; Wani, Shameem; Wani, Zaffer Nowshad (International Journal of Research in Medical Sciences, 2019)
Background: Timely diagnosis and treatment of tuberculosis is important to treat the disease and to reduce transmission. The WHO recommends using GeneXpert MTB in developing, high-burden countries. A study was conducted to evaluate the performance of Xpert assay for the detection of M. tuberculosis and rifampicin resistance in clinical specimen. Methods: About 615 consecutive samples were simultaneously subjected to culture and phenotypic drug susceptibility test for M. tuberculosis and analysis by GeneXpert assay. Confirmed Mycobacterium tuberculosis in a positive culture was used as a reference standard for TB diagnosis. Results: The assay achieved a sensitivity of 96.75% (268/277) and 76.47% (26/34) for smear positive and smear negative pulmonary specimen respectively. In extrapulmonary specimen, the sensitivity was 50% (1/2) and 42.8% (3/7) for smear positive and smear negative specimen respectively. An additional 48 M. tuberculosis were detected by Xpert assay which were smear and culture negative. The Xpert assay identified 100% of the phenotypic rifampicin susceptible isolates and 74.19% of the phenotypic rifampicin resistant isolates. Discordant results were seen in 8 (2.76%) isolates. 6 of these isolates were confirmed to be rifampicin resistant by the reference lab. Conclusions: Present study indicates that Xpert MTB/RIF assay is an effective and rapid tool for the rapid diagnosis of Mycobacterium tuberculosis. The sensitivity is comparable to culture in smear positive specimen but less sensitive than culture for smear negative specimen. In cases with high index of suspicion or discordance for rifampicin results, confirmation should be done by other methods due to false negative results on Xpert assay.